NURSING CARE OF PATIENTS WITH ABSCESS IN THE DEPARTMENT OF TRAUMATOLOGY AND ORTHOPEDICS AT VIET TIEP FRIENDSHIP HOSPITAL IN 2025. (Vietnam Journal of Community Medicine, 2026)
Objective: This study aimed to describe the current situation of care for patients with soft tissue abscesses and to identify several related factors.Method: A cross-sectional descriptive study was conducted on 229 abscess patients treated at the Department of Orthopedic Trauma Surgery, Viet Tiep Friendship Hospital from March 1, 2025 to August 30, 2025.Results: The results showed that the majority of patients diagnosed and treated for abscesses were aged 60 years or older (42.9%). The leading cause of abscesses was infection (55.9%). Factors such as diabetes, obesity, and burns were associated with medical and surgical care with p < 0.05.Conclusion: Diabetes mellitus, as well as a history of burns or trauma, were found to be associated with the quality and process of abscess care.
Keywords: Soft tissue abscess, care, surgery